Implementation of Islamic Universal Values-based Leadership Power at State Islamic Higher Education - Andik Rony Irawan; Triyo Supriyatno; Faizal Rois Fatahillah (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
Islamic leaders employ a range of leadership styles, from transformational to charismatic styles. In response to environmental changes, society has begun to reject various styles because of the demonstration of some of each style's faults. This study aimed at introducing an Islamic universal values-based leadership power (IUVLP) style that involves four leaders at UIN Maulana Malik Ibrahim Malang. Data were collected using interviews, observation, and documentation. Data were analyzed using qualitative analysis descriptive. The results show that there is a significant difference in IUVLP practices according to understanding, appreciation, and experience. However, there exists a significant relationship between IUVLP and Leaders' working experience. For the Leader’s practice priority, the research has found that community-based leaders are the most commonly practiced IUVLP dimension of Islamic Leadership. It is followed by the demonstration of fairness, sincerity, respect, and serving others. The major implication is that experienced Leaders frequently practiced IUVLP compared to less experienced Leaders. Hence, the selection of Leaders should be based on their achievement, not seniority in the Islamic higher education service.